Programa de cuentos pictográficos para incrementar el lenguaje oral en niños(as) de 3 años de una institución educativa del Callao - Saldaña Monago, Rossana del Pilar (2012)
This experimental study was aimed to test the effectiveness of a program to increase the level of spoken language in three year old children by using stories with pictograms as a methodological strategy. The instrument used was the spoken language Test of Navarra Revised (2004) of Aguinaga, Armentía, Fraile, Ollangua and Uriz. The program was applied for three months to 17 children, both genders, who were at a level of needs had been sated at poor or needs improvement (experimental group). The control group was formed of 15 children with the same characteristics as the experimental group who did not received the program. The post-test proved the effectiveness of the program since the children from the experimental group improved significantly their spoken language in the dimensions of form, content and use.